PROCESS APPROACH IN THE OPERATIONS OF THE LOGISTICS SERVICES MANAGEMENTS OF VENEZUELA PETROLEUM - Hernández Gil, Calixto; Nava Quintero, Wuilliams (Revista Arbitrada Formación Gerencial, 2024)
The objective of there search was to characterize the process approach in the operations of the logistics services management of Petróleos de Venezuela. The study was descriptive, with a non-experimental, transectional and field design. The population was made up of the management of Venezuelan oil logistics services on the Eastern coast of the Lake. For data collection, the survey technique was applied, with a questionnaire containing 16 items. Validation was carried out through the judgment of 5 experts, and reliability was calculated through Cronbach's Alpha coefficient, obtaining 0.94, placingit at very high reliability. The results showed high compliance with the process approach in the managements studied, given by very high compliance in the input indicators, process activities, resources, controls and output, representing a strength for management.